2021
DOI: 10.1167/iovs.62.2.23
|View full text |Cite
|
Sign up to set email alerts
|

The Flash-lag Effect in Amblyopia

Abstract: Purpose Amblyopes suffer a defect in temporal processing, presumably because of a neural delay in their visual processing. By measuring flash-lag effect (FLE), we investigate whether the amblyopic visual system could compensate for the intrinsic neural delay due to visual information transmissions from the retina to the cortex. Methods Eleven adults with amblyopia and 11 controls with normal vision participated in this study. We assessed the monocular FLE magnitude for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 67 publications
1
5
0
2
Order By: Relevance
“…Actually, by using the FLE and the FGE, we previously investigated how the amblyopic visual system implements motion extrapolation within the monocular visual processing stage. 23 , 24 In addition, we also found that patients with amblyopia exhibit a smaller FLE and a larger FGE both in their AE and FE. Such reduced FLE would characterize less anticipation of the position of the moving object along its trajectory.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…Actually, by using the FLE and the FGE, we previously investigated how the amblyopic visual system implements motion extrapolation within the monocular visual processing stage. 23 , 24 In addition, we also found that patients with amblyopia exhibit a smaller FLE and a larger FGE both in their AE and FE. Such reduced FLE would characterize less anticipation of the position of the moving object along its trajectory.…”
supporting
confidence: 63%
“…4 A), suggesting impaired motion extrapolation in the amblyopic visual system, consistent with our previous studies using monocular viewing. 23 , 24 In addition, we found a shallower slope of the psychometric function in the AE compared with that in the NDE (see Fig. 4 B).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Этот препарат обладает холинэргическими и нейропротекторными свойствами, участвует в метаболизме фосфолипидов, тем самым защищает структурную целостность клеточных мембран и предотвращает повреждение нервных клеток. В неврологии он применяется в период восстановления после нарушения мозгового кровообращения, в офтальмологии -при глаукоме [9]. У взрослых пациентов с амблиопией цитиколин применялся в комбинации с окклюзионной терапией, было отмечено улучшение остроты зрения, но эффект был нестойким и ограничивался периодом применения препарата.…”
Section: медикаментозная терапия амблиопииunclassified
“… 2 , 13 , 14 , 15 An important example of ocular imbalance is amblyopia, a developmental condition resulting from the abnormal development of the visual system in the early stages of life, 16 characterized by a unilateral decrease in various spatial resolution dysfunctions, 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 the presence of spatial crowding, 25 and reduced temporal functions. 24 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 Indeed, various studies have shown that binocular imbalance in the spatial or stimulus energy domain is associated with lower binocular summation, 13 , 15 , 38 , 39 , 40 which is restored by adjusting the contrast or stimulus energy of the two eyes. 39 , 41 …”
Section: Introductionmentioning
confidence: 99%